Nontrivial spatial dependence of the spin torques in L10 FePt-based tunneling junctions - Sanvito, Stefano; Galante, Mario; Ellis, Matthew O.A. (My University, 2019)
We present an ab initio study of the spin-transfer torque in Fe/MgO/FePt/Fe magnetic tunnel junctions. We consider an FePt film with a thickness up to six unit cells, either in direct contact with the MgO spacer or with an intercalated ultrathin Fe seed layer. We find that in the FePt layer the torque is not attenuated as strongly as in the case of pure Fe. Moreover, in FePt the torque alternates sign at the Fe and Pt atomic planes throughout the stack for all FePt thicknesses considered. Finally, when Fe is intercalated between MgO and L10 FePt, the torque is sharply attenuated, and it is transferred to FePt only for an Fe seed layer that is less than two atomic planes thick. We attribute these features to the different spatial profiles of the exchange and correlation field and the induced nonequilibrium spin accumulation. The calculated tunneling magnetoresistance of the Fe/MgO/FePt/Fe junctions studied is enhanced with respect to the one of Fe/MgO/Fe, while it is reduced with Fe intercalation. Our work shows that L10 FePt junctions can be promising candidates for current-operated magnetic devices and that the magnetic texture at the atomic scale has an important effect on the spin-transfer torque.
PUBLISHED
Keywords: Magnetic tunnel junctions; First-principles calculations; Spin transfer torque; Density functional theory; Nonequilibrium Green's function